Cardiac Mineralocorticoid Receptor and the Na+/H+ Exchanger: Spilling the Beans - Ennis, Irene Lucía; Pérez, Néstor Gustavo (Frontiers in Cardiovascular Medicine, 2021)
Current evidence revealed that cardiac mineralocorticoid receptor (MR) activation following myocardial stretch plays an important physiological role to adapt developed force to sudden changes in hemodynamic conditions. Its underlying mechanism involves a previously unknown non-genomic effect of the MR that triggers redox-mediated Na+/H+ exchanger (NHE1) activation, intracellular Na+ accumulation, and a consequent increase in Ca2+ transient amplitude through reverse Na+/Ca2+ exchange. However, clinical evidence assigns a detrimental role to MR activation in the pathogenesis of severe cardiac diseases like congestive heart failure. This mini review was meant to present and briefly discuss some recent discoveries about locally triggered cardiac MR signals, with the objective of shedding some light on its physiological but potentially pathological consequences in the heart.